Sustainability as a stumbling block in closing acquisitions? The joint effect of target and acquirer ESG performance on time to completion - Just, Ruben; Sommer, Friedrich; Heubeck, Tim; Meckl, Reinhard (Finance Research Letters, 2023)
Sustainability is currently a major concern in business and society. As environmental, social, and governance (ESG) aspects are also considered in acquisitions, e.g., through time-consuming ESG due diligences, we investigate whether differences in ESG performance delay the closing of acquisitions. Using a sample of global M&A transactions, we measure ESG performance using the Refinitiv Eikon ESG scores and time to completion (TTC) as the number of days between the announcement and closing of a transaction. Our results show that larger differences in ESG performance between acquirer and target lead to shorter TTC when acquirer ESG performance exceeds target ESG performance.
CRIS-Team Scopus Importer:2025-09-22
Keywords: Due diligence; ESG; M&A; Sustainability; Time to completion